Untangling the reproductive puzzle: how floral traits, pollinator behavior, and breeding strategy shape reproductive success in the Himalayan medicinal herb Phytolacca acinosa Roxb - Magray, Junaid A.; Wani, Bilal A.; Nawchoo, Irshad A.; Ganie, Aijaz H.; Javid, Hanan; Qadir, Roof Ul (Frontiers in Plant Science, 2025)
Understanding the reproductive ecology of plants is crucial for devising strategies for their sustainable utilization and effective conservation. In this context, the present study investigates the reproductive biology of Phytolacca acinosa, a multipurpose medicinal herb of the Himalaya. The study aimed to examine the floral and pollen biology, breeding behavior, and pollination ecology of the species to inform conservation strategies. The results showed significant variation in floral traits across sites along an elevational gradient, reflecting reproductive adaptation to varying environmental conditions. Pollen grains were found to be tricolpate, prolate, and ellipsoidal. The pollen–ovule ratio indicates a facultative xenogamous breeding system is operative in the target species. Reproductive indices, including the outcrossing index (OCI), self-incompatibility index (SI), and selfing rate (S), along with bagging experiments, revealed that the species is both self and cross-compatible. Moreover, Phytolacca acinosa exhibits a mixed mating strategy, favoring geitonogamy over xenogamy. The pollination syndrome is ambophilous, with generalist pollinators—mainly from the order Hymenoptera—playing a dominant role. Based on insect visitation efficiency and pollen load on insect body, Crabronidae and Apis cerana indica were identified as the most effective pollinators. Although the inflorescence architecture, stigmatic movement, and likely apocarpous nature favor geitonogamy, the breeding system of P. acinosa does not conform strictly to a particular evolutionary strategy, oscillating between selfing and outcrossing. Overall, the findings offer valuable insights that will contribute to the development of effective conservation and sustainable utilization strategies for this high-value medicinal species.